Structural analysis at the southern end of the Central Precordillera of San Juan - Giampaoli, P. (2003)
The Central Precordillera of San Juan is a thin-skinned fold and thrust belt bounded to the east by the thick-skinned structures of the Eastern Precordillera. The objective of this study is to describe and interpret the structural features found at the southern end of this fold and thrust belt. The lomas de Andapaico's folds are of asymmetric, open chevron type, and are genetically related to fault propagation. Toward the north, the folding becomes tighter and broken by faults. The regional structure consists of an imbricated fan of an array of separated to overlapping fault propagation folds, and out-of-sequence structures related to the Eastern Precordillera uplift. The major décollement thrust is located near the top of the San Juan Formation limestone. Deformation occurred in two main stages. First, an imbricate array of fault-propagation folds was developed as the thrust front migrated toward the foreland. Then, the uplift of the eastern Precordillera impeded the migration of the thrust front and may have caused the development of out-of-sequence structures in the Central Precordillera. The minimum horizontal shortening calculated is 4.8 km, and the whole structure shows a southward decreasing shortening that is shown by structures of different orders and a variety of styles of deformation.